Growth and yield of some promising Egyptian rice genotypes under foliar application of different stimulating compounds - Mohamed, A A E; Sorour, S Gh R; Metwally, T F; Elsayed, Gh A (ORYZA-An International Journal of Rice, 2022)
The Effects of foliar application of different stimulating compounds on the growth and yield of three promising Egyptian rice genotypes were studied in a field experiments at the Experimental Farm of Rice Research and Training Center (RRTC), Egypt, during consecutive rice seasons 2018 and 2019. Three rice Egyptian genotypes (Sakha108, GZ9399, and GZ10154) were tested under different stimulating compounds like Ascobine (13% citric acid, 25% ascorbic acid plus 62% organic materials), humic acid (65% humic acid +10% K2O), Amino acid (27.38 % mixed amino acid + 9% micronutrients + 2% magnesium), vulvic acid (50% Vulvic acid + 20% organic acid), N:P:K::20:20:20 and potassium sulphate (50% K2O) The growth characteristics like number of tillers, chlorophyll content, leaf area and dry matter accumulation at 30 and 45 days after transplanting were determined . Number of panicles m-2, panicle length, panicle weight, 1000-grain weight, number of filled grains per panicle, number of unfilled grains per panicle, grain yield and straw yield were studied at harvest. There were significant variations among the studied genotypes in terms of the studied characteristics like (chlorophyll content and grain yield). The foliar application of stimulating compounds significantly increased growth, yield and yield components of the studied rice genotypes. There were significant differences among the response of the studied genotypes to the application of the stimulating compounds. Application of amino acid to Sakha108 recorded the highest grain yield.